'Zulu Identities: Being Zulu, Past and Present.' Edited by Benedict Carton, John Laband and Jabulani Sithole. - Mulaudzi, Maanda (Kronos: Southern African Histories, 2017)
Zulu Identities interrogates assumptions about identity and extends revisionist scholarship on Zulu history and identity. Divided into six overlapping sections and comprising over fifty chapters with contributions by as many authors, the book 'explores the cultural alchemy of ubuZulu bethu, an idiom ... that captures the shared narratives, hybrid expressions and contradictory meanings of "our Zuluness'" (4). Although historians outnumber other contributors, the editors have deliberately sought an inter-disciplinary approach that explores Zuluness in a variety of sites, both the obvious and the obscure. Equally